The clinical use of impulse oscillometry in neuromuscular diseases. (August 2022) - Iliaz, Sinem; Yunisova, Gulshan; Cakmak, Ozgur Oztop; Celebi, Ozlem; Bulus, Eser; Duman, Arda; Bayraktaroglu, Mesut; Oflazer, Piraye
Abstract: Background: The patients with neuromuscular diseases (NMD) are very fragile and it is hard to evaluate respiratory involvement of the primary disease in this group. Therefore, our study aimed to reveal the relationship between pulmonary function tests (PFT) and impulse oscillometry (IOS) and their correlation with respiratory clinical findings in NMD. Material and methods: A total of 86 consecutive patients with NMD were included. The clinical findings of respiratory involvement, PFT, and IOS results of the patients were analyzed. Results: Forty patients out of 86 were female. There were 29 patients with amyotrophic lateral sclerosis, four patients with myasthenia gravis, and 53 patients with muscular dystrophies/myopathies. According to the PFT results, 47 patients had restrictive PFT. However, there was no difference in IOS parameters when we compared the patients according to restrictions in PFT. A positive correlation was found with FVC %pred and X5 . PEF %pred values were positively correlated with X10, X15, and X20, and negatively correlated with AX and R5-20 . The patients with worse swallowing capability had increased Rrs levels, and more negative Xrs levels. The shortness of breath led to lower FEV1 %pred., higher R5, AX and R5-20, and also more negative X10, X15, and X35 . Conclusion: Clinically reported dysphagia, a decreased capability of coughing, and shortness of breath in patients with NMD make Rrs increase in general, but Xrs parameters, which mainly express rib cage elasticity, turn more negative. In patients with NMD, IOS monitoring may help in evaluating the regression in respiratory functions, however, future studies are needed to understand more. Highlights: The largest study on impulse oscilometry (IOS) in neuromuscular disorder (NMD). Functional disabilities lead increase in Rrs and Xrs turn more negative in NMD. Use consecutive IOS tests to evaluate the progression of respiratory involvement. The study adds on the literature by supporting reference data for IOS in NMD.